A comparative study of stent thrombectomy and direct aspiration thrombectomy in the treatment of ischemic stroke caused by acute middle cerebral artery M2 segment occlusion - GUO Zhang⁃bao; XU Xiang⁃qian; CHEN Min; DUAN Zhen⁃hui; TANG Kun; LIU Wen⁃hua (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Objective To analyze the effectivity and safety of stent thrombectomy and direct aspiration thrombectomy in the treatment of ischemic stroke caused by acute middle cerebral artery (MCA) M2 segment occlusion. Methods A total of 44 patients with ischemic stroke caused by acute MCA M2 segment occlusion who received endovascular therapy in Wuhan No.1 Hospital from March 2016 to March 2021 were selected, including 22 patients with stent thrombectomy and 22 patients with direct aspiration thrombectomy. Time from onset to the end of surgery, postoperative immediate recanalization rate [modified Thrombolysis in Cerebral Infarction Score (mTICI)≥2b], postoperative 90⁃day good prognosis rate [modified Rankin Scale（mRS）≤2], mortality, rate of symptomatic intracranial hemorrhage (sICH) and asymptomatic intracranial hemorrhage (asICH) were recorded. Results The postoperative recanalization rate in the total 44 patients was 77.27% (34/44), while 68.18% (15/22) in the stent group and 86.36% (19/22) in the aspiration group. Five patients in the aspiration group had poor result with aspiration and were remedied with stent thrombectomy. There was no statistic difference in the time from puncture to the end of the surgery (t=0.978, P=0.334), recanalization rate (χ2=2.071, P=0.150), postoperaitve 90⁃day good prognosis rate (χ2=0.364, P=0.546), mortality (χ2=0.193, P=0.660), incidence of sICH (χ2=0.524, P=0.469) and asICH (χ2=0.275, P=0.600). Conclusions This preliminary study showed that stent thrombectomy and direct aspiration thrombectomy in patients with ischemic stroke caused by acute MCA M2 segment occlusion are safe and effective, but further exploration of multicentre, large⁃sample randomised controlled trials is needed.